The role of vitamin D in children with recurrent Tonsillopharyngitis - Yildiz Ismail; Unuvar Emin; Zeybek Umit; Toptas Bahar; Cacina Canan; Toprak Sadık; Kilic Ayse; Aydin Salih (BMC, 2012)
Abstract Background The exact etiology of recurrent tonsillopharyngitis in children is not clear. Recurrent tonsillitis in children has multifactorial etiology like most of the diseases in childhood. In this study, our aim was to determine the potential role of vitamin D in recurrent tonsillitis by measuring serum 25-OH vitamin D levels and determining the vitamin D receptor polymorphism among children with recurrent tonsillitis. Methods Eighty-four children with recurrent tonsillitis and seventy-one healthy children aging between 2 and 10 years were enrolled in this study. Serum 25-OH vitamin D level was measured with ELISA and vitamin D receptor gene polymorphism (Apa1, Taq 1, Fok1) was determined by PCR. Serum 25-OH vitamin D level below 50 nmol/L was accepted as deficiency. The vitamin D receptor gene polymorphism in each group was compared. Results The mean age was 5.6 ± 2.4 and 6.1 ± 2.7 years in study and control group, respectively. The average serum 25-OH vitamin D level was 142.7 ± 68.1 nmol/L in study group and 192.3 ± 56.1 nmol/L in control group. There was significant difference between the groups (p < 0.01). In study group, 4.7% (n = 4) of children had serum 25 OH vitamin D levels below 50 nmol/L. None of the children in control group had serum 25-OH vitamin D level below 50 nmol/L. There was no significant differences in vitamin D receptor gene polymorphisms between groups. Conclusion Serum 25-OH vitamin D levels in recurrent tonsillitis group were lower than those in healthy children. But, there was no difference in the incidence of vitamin D receptor gene polymorphism between the two groups.